Effectiveness of COVID-19 vaccines against SARS-CoV-2 infection and severe outcomes in adults: a systematic review and meta-analysis of European studies published up to 22 January 2024 - Zhou, Guiling; Dael, Nina; Verweij, Stefan; Balafas, Spyros; Mubarik, Sumaira; Rengerink, Katrien Oude; Pasmooij, Anna Maria Gerdina; van Baarle, Debbie; Mol, Peter G.M.; de Bock, Geertruida H.; Hak, Eelko (European Respiratory Society, 2025)
Background Up-to-date evidence from European studies on long-term vaccine effectiveness (VE) of COVID-19 vaccines is lacking. This review aimed to evaluate effectiveness and durability of primary vaccine series and boosters in preventing infection and severe outcomes in the European population. Methods We conducted systematic searches of PubMed and Embase up to 22 January 2024. We included observational studies that evaluated VE against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection or severe disease (hospitalisation, intensive care unit admission or death) for primary series and boosters in Europe. We applied a random-effects meta-analysis model. Results We included 33 studies and over 56 million participants. The overall VE of the complete primary series against infection with any SARS-CoV-2 variant was 70.7%. VE was lower for Omicron, at 26.1%, than for pre-Omicron strains, at 77.0%. Over time, VE against infection by any variant decreased from 68.9% to 38.9% after 6 months. Boosters restored VE to 76.4% and maintained at 58.4% after 3 months. The overall VE of a complete primary series for severe outcomes due to any variant was 87.4%, with 93.3% for pre-Omicron and 62.8% for Omicron strains. Protection against severe outcomes declined less than for infection. 6 months after the primary series, the vaccine still provided over 50% protection against severe outcomes caused by Omicron. Boosters restored VE to 87.9% and maintained at 78.5% after 3 months. Conclusion VE against SARS-CoV-2 infection declines markedly with time and Omicron variants. Protection against severe outcomes was more durable and resistant to viral mutation. Boosters restored protection, emphasising the need for timely booster vaccination for vulnerable populations.
Keywords: Pulmonary and Respiratory Medicine; SDG 3 - Good Health and Well-being